Diagnosis of adverse events after hysterectomy with postoperative self-care web applications: A pilot study. (December 2017) - Gilmour, Donna T; MacDonald, Norman J; Dukeshire, Steven; Whynot, Barbara; Sanders, Barry; Thiel, John; Singh, Sony; Campbell, Craig; Bajzak, Krisztina; Flowerdew, Gordon
Increased pressures from multiple sources are leading to earlier patient discharge following surgery. Our objective was to test the feasibility of self-care web applications to inform women if, when, and where to seek help for symptoms after hysterectomy. We asked 31 women recovering at home after hysterectomy at two centers to sign into a website on a schedule. For each session, the website informed them about normal postoperative symptoms and prompted them to complete an interactive symptom questionnaire that provided detailed information on flagged responses. We interviewed eight women who experienced an adverse event. Six of these women had used the web application regularly, each indicating they used the information to guide them in seeking care for their complications. These data support that self-care applications may empower patients to manage their own care and present to appropriate health care providers and venues when they experience abnormal symptoms.